Mie Scattering Revisited: Study of Bichromatic Mie Scattering of Electromagnetic Waves by a Distribution of Spherical Particles - Olivares-Bahamondes, I (American Institute of Physics, 2020)
Two experiments to measure the size of microscopic dielectric spherical particles immersed in purified water with spheres of a nominal diameter 5.2 ± 0.15 μm have been carried out in order to revisit Mie scattering techniques. The first experiment uses a 1 mW helium-neon (He-Ne) laser with a wavelength of 632.8 nm, while the second one is carried out using a diode laser of 780.0 nm wavelength and a nominal power of 80 mW. The distribution of the scattered light intensity is recorded experimentally, and since the theoretical background has been known for several decades (see references), only a modest amount of theory is included. We considered the Mie scattering by a set of spheres of different diameters in our case with a distribution of sphere diameters with mean diameter 5.2 μm and standard deviation 0.15 μm. Our measured Mie scattering angular distribution accounts for the effect of the diameter distribution, which we assume to be a Gaussian distribution. Our results indicate that there is very good agreement between experiment and theoretical predictions. The technique we offer here is found to be useful to familiarize technicians who work in the areas of applied optics, such as chemistry, electronics, water contamination, and optical instruments with Mie scattering techniques, and who may not have a formal introduction to the electromagnetic theory. One specific area in which these techniques might be useful is the study of aerosols that may arise when naturally produced droplets from humans, such as those produced by coughing, sneezing, talking, and breathing, are present, as it happens in response to the Severe Acute Respiratory Syndrome Coronavirus 2, also known as SARS-CoV-2. © 2020 Author(s).